2022
DOI: 10.1039/d2qo00487a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free synthesis of sulfonylated indolo[2,1-a]isoquinolines from sulfur dioxide

Abstract: Access to sulfonylated indolo[2,1-a]isoquinolines through an efficient three-component reaction of 2-aryl-N-acryloyl indoles, sulfur dioxide and aryldiazonium tetrafluoroborates is developed. This transformation is performed under metal-free and mild conditions by using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…In 2019, Lee reported an electrochemical synthetic protocol for the sulfonylation of tertiary amines toward β-amido-vinyl sulfones, using sulfonyl hydrazides (81) and tertiary amines (82) as substrates (Scheme 11). 67 To realize the protocol, the substrates were treated in an undivided cell equipped with a graphite anode and a Pt cathode with a constant current of 5 mA (6.2 F mol −1 ) in DMSO under an acidic condition (acetic acid).…”
Section: Sulfonylation Of Alkenes and Alkynesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Lee reported an electrochemical synthetic protocol for the sulfonylation of tertiary amines toward β-amido-vinyl sulfones, using sulfonyl hydrazides (81) and tertiary amines (82) as substrates (Scheme 11). 67 To realize the protocol, the substrates were treated in an undivided cell equipped with a graphite anode and a Pt cathode with a constant current of 5 mA (6.2 F mol −1 ) in DMSO under an acidic condition (acetic acid).…”
Section: Sulfonylation Of Alkenes and Alkynesmentioning
confidence: 99%
“…It was indicated that the key steps in this reaction involved sulfonyl radical's addition to alkene, which was generated by the electro-oxidation of tertiary amines in situ. At the early stage, sulfonyl hydrazides (81) and tertiary amines (82) were oxidized at the anode and gave sulfonyl radicals (84) and alkenes (87) respectively, and then the addition took place and yielded carbon radical intermediates (88). Then the intermediates (88) underwent with an oxidation and elimination sequence and afforded the target compounds.…”
Section: Sulfonylation Of Alkenes and Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an active nitrogen-containing heterocyclic skeleton, indole exists widely in biologically active natural products and synthetic bioactive products, and represents an important “privileged scaffold”. 1 Among the numerous indoles, 3-arylselenoindoles are particularly attractive due to their potential use in therapeutics such as anti-oxidant, anti-tumor, and anti-cancer agents. 2 For example, as a novel combretastatin-like drug, 3-selenylindole compound (I) exhibits highly potent inhibitory activity against cancer cells 3 ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a variety of protocols have been developed to construct β-keto sulfones. 8 Whereas succinct synthetic routes toward structurally related γ-keto sulfones are scarce, 9 traditionally, γ-keto sulfones were synthesized via the nucleophilic substitution of sodium sulfinates by 2-chlorovinyl ketones, 10 the elimination of the bromo derivatives of saturated keto sulfones 11 and the oxidation of the corresponding sulfides or sulfoxides. 12 However, the principal drawback is that these procedures were strongly limited by multiple steps, narrow substrate scope, or poor stereoselectivity.…”
mentioning
confidence: 99%